The global prevalence of native and non-native plants in urban areas - Andressa L.L. Luna; Renata Trevizan; Camila Bosenbecker; Victor H.D. Silva; Ingrid N. Gomes; Carlos A. Ordóñez-Parra; Bruna Nascimento; Pedro A. Anselmo; Flávia S. Faria; Teresa M. Fonseca; Ricardo R.C. Solar; Tatiana G. Cornelissen; et al. (Landscape and Urban Planning, 2026)

A systematic review of the land use change effects on ant diversity in Neotropics - Icaro Wilker; Antônio C.M. Queiroz; Carla R. Ribas; Maria Santina C. Morini; Chaim J. Lasmar; Fernando A. Schmidt; Rodrigo M. Feitosa; Anselmo Nogueira; Fabrício B. Baccaro; Mônica A. Ulysséa; Thiago Izzo; Lucas N. Paolucci; et al. (Biological Conservation, 2024)

An analysis of the cecum microbiome of three breeds of the guinea pig: Andina, Inti, and Peru - Hugo Frias; Nilton Luis Murga Valderrama; Gary J. Flores; Victor G. Cornejo; Jakson Ch. Del Solar; Ana C. Romani; William Bardales; G.T. Segura; Richard C. Polveiro; Dielson da S. Vieira; Rainer M. Lopez Lapa; Jorge Luis Maicelo Quintana (Research in Veterinary Science, 2023)

Ants of Brazil: an overview based on 50 years of diversity studies - Rodrigo M. Feitosa; Gabriela P. Camacho; Thiago S. R. Silva; Mônica A. Ulysséa; Natalia Ladino; Aline M. Oliveira; Emília Z. Albuquerque; Fernando A. Schmidt; Carla R. Ribas; Anselmo Nogueira; Fabrício B. Baccaro; Antônio C. M. Queiroz; et al. (Systematics and Biodiversity, 2022)

Ant diversity studies in Brazil: an overview of the myrmecological research in a megadiverse country - F. A. Schmidt; C. R. Ribas; R. M. Feitosa; F. B. Baccaro; A. C. M. de Queiroz; T. G. Sobrinho; Y. Quinet; K. S. Carvalho; T. Izzo; M. S. de Castro Morini; A. Nogueira; H. M. Torezan-Silingardi; et al. (Insectes Sociaux, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

How much leaf area do insects eat? A data set of insect herbivory sampled globally with a standardized protocol - Gisele M. Mendes; Fernando A. O. Silveira; Carolina Oliveira; Wesley Dáttilo; Roger Guevara; Betsabé Ruiz‐Guerra; Maria Gabriela Boaventura; Sershen; Syd Ramdhani; Shyam S. Phartyal; Sérvio P. Ribeiro; Victor Diniz Pinto; et al. (Ecology, 2021)
Herbivory is ubiquitous. Despite being a potential driver of plant distribution and performance, herbivory remains largely undocumented. Some early attempts have been made to review, globally, how much leaf area is removed through insect feeding. Kozlov et al., in one of the most comprehensive reviews regarding global patterns of herbivory, have compiled published studies regarding foliar removal and sampled data on global herbivory levels using a standardized protocol. However, in the review by Kozlov et al., only 15 sampling sites, comprising 33 plant species, were evaluated in tropical areas around the globe. In Brazil, which ranks first in terms of plant biodiversity, with a total of 46,097 species, almost half (43%) being endemic, a single data point was sampled, covering only two plant species. In an attempt to increase knowledge regarding herbivory in tropical plant species and to provide the raw data needed to test general hypotheses related to plant–herbivore interactions across large spatial scales, we proposed a joint, collaborative network to evaluate tropical herbivory. This network allowed us to update and expand the data on insect herbivory in tropical and temperate plant species. Our data set, collected with a standardized protocol, covers 45 sampling sites from nine countries and includes leaf herbivory measurements of 57,239 leaves from 209 species of vascular plants belonging to 65 families from tropical and temperate regions. They expand previous data sets by including a total of 32 sampling sites from tropical areas around the globe, comprising 152 species, 146 of them being sampled in Brazil. For temperate areas, it includes 13 sampling sites, comprising 59 species. Thus, when compared to the most recent comprehensive review of insect herbivory (Kozlov et al.), our data set has increased the base of available data for the tropical plants more than 460% (from 33 to 152 species) and the Brazilian sampling was increased 7,300% (from 2 to 146 species). Data on precise levels of herbivory are presented for more than 57,000 leaves worldwide. There are no copyright restrictions. Please cite this paper when using the current data in publications; the authors request to be informed how the data is used in the publications.

Ant removal distance, but not seed manipulation and deposition site increases the establishment of a myrmecochorous plant - Tiago V. Fernandes; Lucas N. Paolucci; Ricardo R. C. Solar; Frederico S. Neves; Ricardo I. Campos (Oecologia, 2020)

Vegetation cover of Brazil in the last 21 ka: New insights into the Amazonian refugia and Pleistocenic arc hypotheses - Daniel M. Arruda; Carlos E. G. R. Schaefer; Rúbia S. Fonseca; Ricardo R. C. Solar; Elpídio I. Fernandes‐Filho (Global Ecology and Biogeography, 2018)
Aim The two main hypotheses about the Neotropical palaeovegetation, namely that of Amazonian refugia by Haffer and of the Pleistocene arc by Prado and Gibbs, are still constantly debated. We offer new insights on this debate using ecological niche modelling with combined climate–soil predictors to test both hypotheses, reconstruct the palaeovegetation of the Last Glacial Maximum (LGM; 21 ka) and Mid‐Holocene (Mid‐H; 6 ka) and indicate the configuration of refugia areas. Location Brazil. Time period Last 21 ka. Major taxa studied Biomes. Methods We modelled the environmental space of the 10 most representative biomes with the RandomForest classifier, using climate predictors from three atmospheric general circulation models (CCSM4, MPI‐ESM‐P and MIROC‐ESM) and soil predictors, the same for the different situations. Based on the consensus among the models, we reconstructed the palaeovegetation cover for LGM and Mid‐H and used fossil pollen sites to validate the reconstructions in a direct comparison. Results The climate in the past was cooler and wetter throughout most of the territory. The Amazon basin region was the most affected by climate change in the last 21 ka, with equatorial rain forest retracting to refugia areas, while the tropical rain forest (with climatic preferences similar to the Atlantic forest) expanded in the basin. In southern Brazil, the mixed forest ( Araucaria forest) shifted to lower latitudes, while the grasslands expanded. In most biomes, the greatest changes occurred in the ecotonal zones, supported by pollen fossils. Main conclusions With regard to Haffer's hypothesis, the forests of the Amazonian lowlands retreated to refugia areas, while the colder and wetter climate of the basin created a favourable niche for another type of forest, instead of savanna. The advance of dry vegetation was restricted to ecotonal conditions, preventing the formation of a continuous Pleistocene arc, predicted by Prado and Gibbs's hypothesis.

Phenotypic and Genotypic Diversity of European Chestnut (Castanea sativa Mill.) in Slovenia – Opportunity for Genetic Improvement - A. Solar; A. Podjavoršek; F. S. Štampar (Genetic Resources and Crop Evolution, 2005)

Radiolytic Degradation of the Herbicide Dicamba for Environmental Protection - P. Drzewicz; P. Gehringer; A. Bojanowska-Czajka; R. Zona; S. Solar; G. Nałcz-Jawecki; J. Sawicki; M. Trojanowicz (Archives of Environmental Contamination and Toxicology, 2005)